2001
DOI: 10.1063/1.1328404
|View full text |Cite
|
Sign up to set email alerts
|

Angular distribution of ejected atoms from Nd:YAG laser irradiating metals

Abstract: A Nd:YAG pulsed laser is employed to irradiate different metals in vacuum at the ECLISSE facility of the Laboratorio Nazionale del Sud, Catania, INFN. Laser pulse energy, 9 ns in width, ranges between 100 and 900 mJ. The ejection of atoms by means of laser irradiation is studied in terms of angular distribution, laser etching yield and film thickness deposited on a substrate. Light elements (Ni, Cu) show an angular distribution that is larger than heavy ones (W, Pb). A theoretical approach, applied to fit expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…Moreover measurements demonstrate that the ion yield depends on the angular position of the IC with respect to the normal to the target surface. The experimental angular distribution data for the ion emission indicate a narrow angular emission centered on the normal to the target surface with a FWHM of about 35 • for both wavelengths, in good agreement with the literature [9]. By knowing the target-collector distance it is possible to evaluate the average velocity and the corresponding average kinetic ion energy, which, at the fluence of 100 J/cm 2 , is of about 0.8 keV at 1 064 nm and 1.6 keV at 532 nm, indicating that the visible photons transfer higher average velocities to the ions.…”
Section: Resultssupporting
confidence: 73%
“…Moreover measurements demonstrate that the ion yield depends on the angular position of the IC with respect to the normal to the target surface. The experimental angular distribution data for the ion emission indicate a narrow angular emission centered on the normal to the target surface with a FWHM of about 35 • for both wavelengths, in good agreement with the literature [9]. By knowing the target-collector distance it is possible to evaluate the average velocity and the corresponding average kinetic ion energy, which, at the fluence of 100 J/cm 2 , is of about 0.8 keV at 1 064 nm and 1.6 keV at 532 nm, indicating that the visible photons transfer higher average velocities to the ions.…”
Section: Resultssupporting
confidence: 73%
“…10,38 Some authors have suggested that the angular distribution becomes increasingly narrow with the atomic mass, 38,41 whereas Akhsakhalyan et al 42 have suggested that volatile materials exhibited a broader distribution than refractory ones. The latter measurements 38,41,42 were performed with the laser wavelength of 1064 nm and at a much higher fluence than considered here. The Anisimov model 16 predicts that, for a given spot, smaller values of the initial cloud thickness Z 0 lead to narrower angular distributions.…”
Section: B the Angular Distribution Of Different Metalsmentioning
confidence: 99%
“…Such ions may be used, e.g., for hybrid ion source for a large accelerator injector, based on the coupling of the laser ion source ͑LIS͒ and electron cyclotron resonance ͑ECR͒ ion source ͑ECLISSE experiment͒, [1][2][3][4] but also for the direct surface modification of solids. [5][6][7][8] Relatively low laser intensities ͑only ϳ1ϫ10 10 W/cm 2 ) are high enough for ion generation.…”
Section: Introductionmentioning
confidence: 99%